The Forecast Accuracy Of Second Board IPOs (1989 – 1994) - Tan, Bee Swan (1997)

(untitled)
The reliability of the earnings forecasts has been a topic of criticism recently since some of the listed companies are found to have documented a large discretipency between the actual and forecast profits. This study intend to substantiate the previously documented evidence on the Initial Public Offerings forecast errors of the Main Board. The IPO for firms listed on the Second Board for the period 1989 to 1994. The companies under study covered a wide range of sectors such as Industrial, Consumer, Construction, Trading/Service and Finance. The forecast accuracy is measured by forecast errors, absolute forecast errors and squared forecast error. The level of forecast accuracy appears to be better for the Second Board listed companies compared to that of Main Board IPOs. The accuracy levels are closed to the developed markets such as United Kingdom, United States and Australia. A multiple regression model was needed to explain the variation in the absolute forecast errors (the dependent variable) with firms characteristics as independent variables. The only variable that showed significant relationship with absolute forecast errors was forecast interval that is the time between the prospectus issued date and the year end of the forecast pertain. Other variables, such as Auditor Choice, Age Size Financial Leverage, Industry sectors were not significant. In general, the findings are consistent with that reported for the Main Board IPOs (Shamser et. al. 1994) and inconsistent with those reported in developed markets.